Analysis on BPJS Kesehatan from Various Disciplines - Asman Abnur (Global Review of Islamic Economics and Business, 2015)
BPJS Kesehatan shall be the Social Security Agency (Badan Penyelenggara Jaminan Sosial) established by the government to provide a Health Security for the people. It constitutes an institution specifically established to organize the social security program in Indonesia according to Law No. 40 of 2004 and Law No. 24 of 2011. Pursuant to Law No. 40 of 2004 concerning National Social Security System, BPJS shall constitute a non-profit legal entity. The BPJS Kesehatan Program began on 1 January 2014. The National Health Security Program (Jaminan Kesehatan Nasional / JKN) initiated by BPJS aims at providing health protection for each participant to obtain healthcare benefits. JKN constitutes a healthcare program to serve the people with medical necessities, Insha Allah, Amiin.